2022
DOI: 10.1007/978-3-031-16245-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Railway Digital Twins and Artificial Intelligence: Challenges and Design Guidelines

Abstract: In the last years, there has been a growing interest in the emerging concept of Digital Twins (DTs) among soJware engineers and researchers. DTs represent a promising paradigm to enhance the predictability, safety, and reliability of cyber-physical systems. They can play a key role in different domains, as it is also witnessed by several ongoing standardisa2on ac2vi2es. However, several challenging issues have to be faced in order to effec2vely adopt DTs, in par2cular when dealing with cri2cal systems. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…As a PoC of the approach described in the previous sections, in this section we provide a case-study that is relevant for IIoT-connected railways, which use smart devices to: deliver services to passengers and train drivers; perform automatic train control and maintenance; and control energy consumption [35]. Modern railways can highly benefit from DT technology, which allows for what-if analyses of critical situations and proactive decision-making [36].…”
Section: The Railway Iiot Proof-of-conceptmentioning
confidence: 99%
“…As a PoC of the approach described in the previous sections, in this section we provide a case-study that is relevant for IIoT-connected railways, which use smart devices to: deliver services to passengers and train drivers; perform automatic train control and maintenance; and control energy consumption [35]. Modern railways can highly benefit from DT technology, which allows for what-if analyses of critical situations and proactive decision-making [36].…”
Section: The Railway Iiot Proof-of-conceptmentioning
confidence: 99%
“…Te authors in [83] discriminated the diference and relationship between conventional trafc simulation and digital twin (DT) in terms of features, functions, input data, modelling, and interaction, and they proposed three-layer technical architecture for DT in intelligent transportation, i.e., data access layer (lowest level), computational simulation layer (middle level), and application management layer (highest level). Te review in [85] showed that most of the digital twin-related publications focused on the railway subdomain maintenance, inspection, and resilience, most of which applied machine learning algorithms and techniques in digital twin to predict failures, detect faults, make automated decisions, supervise train movements, provide information on passenger behavior onboard trains, and monitor health status of railway systems.…”
Section: Papermentioning
confidence: 99%
“…Despite several scopes of DTR to advance the railway, few surveys have been conducted on the topic. Addressing maintenance, the authors in [11] elucidated the challenges and advantages of DT for railways, employing Machine Learning (ML) within the DT framework. Additionally, Condition-Based Maintenance (CBM) in the scope of DTR was explored in [12] and [13].…”
Section: Existing Surveysmentioning
confidence: 99%